2021
DOI: 10.1097/mlr.0000000000001629
|View full text |Cite
|
Sign up to set email alerts
|

Shadow Coaching Improves Patient Experience With Care, But Gains Erode Later

Abstract: Background: Health care organizations strive to improve patient care experiences. Some use one-on-one provider counseling (shadow coaching) to identify and target modifiable provider behaviors.Objective: We examined whether shadow coaching improves patient experience across 44 primary care practices in a large urban Federally Qualified Health Center.Research Design: Seventy-four providers with "medium" (ie, slightly below average) overall provider ratings received coaching and were compared with 246 uncoached … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
25
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

6
0

Authors

Journals

citations
Cited by 10 publications
(26 citation statements)
references
References 87 publications
(166 reference statements)
0
25
0
Order By: Relevance
“…11,[31][32][33] We previously examined patient experience scores before and after coaching that incorporated many features consistent with the literature on successful behavior change (i.e., learnercentered approach, immediate feedback, written recommendations on what skills to practice/behaviors to engage in). 34 We found an immediate improvement in patient experience scores following coaching; however, the gains for coached providers eroded, disappearing after 2.5 years.…”
Section: Introductionmentioning
confidence: 58%
“…11,[31][32][33] We previously examined patient experience scores before and after coaching that incorporated many features consistent with the literature on successful behavior change (i.e., learnercentered approach, immediate feedback, written recommendations on what skills to practice/behaviors to engage in). 34 We found an immediate improvement in patient experience scores following coaching; however, the gains for coached providers eroded, disappearing after 2.5 years.…”
Section: Introductionmentioning
confidence: 58%
“…The evaluation team assessed P4P incentive payments before and after the peer coaching, provider perceptions assessed by survey and in interviews, and the content of the coaching reports given to the coached providers after the coaching sessions. The results showed that coaching improved providers' overall rating and CAHPS communication scores, but these improvements faded over time [25]. The content analysis of the recommendations indicated that the coaching recommendations were split between encouragement of existing behavior and identifying new behaviors.…”
Section: Panel On Evaluating Patient Experience Improvement Strategie...mentioning
confidence: 97%
“…Edgman-Levitan also discussed research that identified several organizational characteristics associated with good patient experiences: governance, leadership, and vision; partnerships with patients and families; human resources and employee engagement; systematic feedback, data management, and goal setting; use of best practices around communication strategies and technology support; and the built environment [24][25][26].…”
Section: What Do We Know From Research About Why and How To Improve P...mentioning
confidence: 99%
See 1 more Smart Citation
“…[35][36][37] Evidence from a recent evaluation study of a large shadow coaching program conducted in a large, urban federally qualified health center (FQHC) in California found statistically significant improvements (2-point, small-to-medium, increase) in coached providers' Clinician and Group CAHPS (CG-CAHPS) Visit Survey 2.0 overall provider rating and provider communication scores immediately after being coached. 38 Shadow coaching at this FQHC was introduced as part of quality monitoring to improve patient care experiences. Each January and July, the FQHC calculated every provider's average 6-month score on the CG-CAHPS overall provider rating (scored from low of 0 to high of 100) based on each provider's adult and/or child patient surveys.…”
mentioning
confidence: 99%